Strategi Promosi Restoran Pulau Sentosa Seafood Market Surabaya dalam Meningkatkan Daya Saing di Pasar Kuliner Surabaya - Rusvian Andana; Bambang Karnain (Jurnal Pengabdian Masyarakat, 2025)
This study Aaims to identify the promotional strategies implemented by Sentosa Seafood Market Surabaya Island Restaurant in increasing competitiveness in the culinary industry. In a competitive market, this restaurant utilizes various promotional approaches such as social media, email marketing, public relations, and SEO optimization on the official website. This study uses observation, interview, and documentation methods during Field Work Lectures (KKL) activities which are carried out directly at the business location. The results show that an integrated digital promotion strategy has succeeded in increasing brand awareness, attracting new customers, and strengthening the loyalty of existing customers. In addition, consistent promotion through social media is able to create a positive image and increase engagement with consumers. The study also highlights the importance of analyzing market trends and utilizing digital technology to reach the target audience more effectively. Based on these results, it is recommended that restaurants continue to improve the use of customer data and social media optimization to achieve better promotional effectiveness and sustainable business growth.